Design and optimization of DPC-crosslinked HPβCD nanosponges for entrectinib oral delivery: formulation, characterization, and pharmacokinetic studies - Konda Sri Chaya Reddy; Darna Bhikshapathi (SpringerOpen, 2024)
Abstract Background In advanced or metastatic cancers characterized by specific genetic alterations, heightened growth and resistance to conventional therapies are common. Targeted treatments like entrectinib (ENT) precisely inhibit aberrant signaling pathways, potentially enhancing outcomes. The objective of this research is to develop and enhance the effectiveness of entrectinib-loaded nanosponge formulations by utilizing hydroxypropyl-β-cyclodextrin (HPβCD) to improve its oral bioavailability. Results The study employed surface response methodology and Design-Expert® software to optimize key formulation variables such as the molar concentration ratio of the polymer and cross-linker, as well as process variables such as stirring speed and duration. Optimization focused on particle size, polydispersity index, and percentage entrapment efficiency. Validation methods encompassed Fourier transform spectroscopy (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), in vitro release studies, and in vivo studies. After optimization, ENT-loaded HPβCD NSPs were formulated with a molar ratio (P:CL) of 0.800 mg, stirred at 3000 rpm for 420 min, achieving a desirability of 0.926. Predicted values for PS (particle size), PdI (polydispersity index), and EE % (entrapment efficiency) were 146.98 nm, 0.263, and 88.29%, respectively. The optimized formulation showed a mean size of 151.8 ± 5.6 nm, PDI of 0.233 ± 0.049, and EE of 87.36 ± 1.61%. Further validation through various analyses confirmed the optimization's efficacy, with notable improvements demonstrated in AUC0-t (6.30-fold) and Cmax (4.10 times) compared to the free drug. Conclusion The findings of the study indicated that nanosponges exhibit promise as an effective carrier for delivering entrectinib, addressing for advance tumor effectively by enhancing release and bioavailability in the treatment of cancer.